Estandarización para la fabricación de madera plástica en la Empresa Ocoplast (2023)
In this internship report, first, the characterization of raw materials used in the manufacturing process of plastic wood was carried out at the Ocoplast plant, a company located in the city of Neiva, a pioneer in the manufacture of this material in Huila and in Colombia. Ocoplast is mainly dedicated to the manufacture of plastic wood for furniture, architectural and all types of industry. It implements raw materials in its production process, mainly from 100% recycling processes. Due to this, there is uncertainty. on the composition of its raw materials. The method was established to be able to define what type of raw materials Ocoplast currently receives and thus be able to establish what types of polymers are those that currently make up its mixture.